Pengelolaan Program Pembelajaran Remidial Bidang Studi Matematika Di Smp Muhammadiyah 6 Tipes, Kota Surakarta - Kurniawan, Ari; , Prof. Dr. Markhamah, M.Hum; , Dr. Sumardi, M.Si (2015)
Remidial learning is learning that is done to the students who have low ability in mastering the knowledge that submitted the teacher in the classroom, especially knowledge learned through certain ways of learning in accordance with the school curriculum. The purpose of this study is to describe the remedial learning management subject areas of Mathematics. Location research is in SMP Muhammadiyah 6 Tipes, Surakarta City. Source of research data obtained from class VIII C. The data obtained with the use observation, interviews with subject teachers and the students Matemetika. Data analysis techniques used in the form of data pengmpulan, redusi, data presentation and conclusion. The validity of the data in this study using data triangulation technique. The results of this study, 1) the difficulty absorption Mathematics subject material by students contains material which is difficult when remedial learning along with a list of names of students who take remedial of learning, types of learning material difficulties experienced by students and the factors that influence why the student is having difficulty absorption material at a time following the remedial learning. 2) remidial learning plan contains plannings are prepared includes learning materials, methods and learning strategies, media and learning resources, step learning, remidial pembelajaaran assessment. 3) material remedial teaching and learning strategies, namely, teaching materials and their remedial learning strategies used in remedial learning includes learning strategies Contextual Teaching Learning (CTL), Inquiry learning strategies, problem-based learning strategies (Problems Solving), group learning and learning strategies. 4) Results and discussion remidial learning lists the names of students who take remedial learning, before remidial value, the value after learning the results of the evaluation of remedial actions and remidial learning mathematics subjects in SMP Muhammadiyah Surakarta 6 Tipes.